Divide 7 by 12
which would give you 0.58
so that’s 58%
<em>Given - a+b+c = 0</em>
<em>To prove that- </em>
<em>a²/bc + b²/ac + c²/ab = 3</em>
<em>Now we know that</em>
<em>when x+y+z = 0,</em>
<em>then x³+y³+z³ = 3xyz</em>
<em>that means</em>
<em> (x³+y³+z³)/xyz = 3 ---- eq 1)</em>
<em>Lets solve for LHS</em>
<em>LHS = a²/bc + b²/ac + c²/ab</em>
<em>we can write it as LHS = a³/abc + b³/abc + c</em><em>³</em><em>/abc</em>
<em>by multiplying missing denominators,</em>
<em>now take common abc from denominator and you'll get,</em>
<em>LHS = (a³+b³+c³)/abc --- eq (2)</em>
<em>Comparing one and two we can say that</em>
<em>(a³+b³+c³)/abc = 3</em>
<em>Hence proved,</em>
<em>a²/bc + b²/ac + c²/ab = 3</em>
You would do 0.25x (x is the unknown total number)=19. It is because of is a multiply sign, so 0.25*x=19. Divide both sides by 0.25 and you get 76 as your answer.
Answer:
The answer is 91.
Step-by-step explanation:
Since 2+2+2=6 and you subtract 2 that would now be 6-2, and that is 4.
87+4=91.
Simply 6-2=4
87+4=91
:)
Answer:
no
Step-by-step explanation:
linear must be straight